Taurine Activates BMP-2/Wnt3a-Mediated Osteoblast Differentiation and Mineralization via Akt and MAPK Signaling - Minsu PARK; Hyeon Kyeong CHOI; Jeung Hee AN (Tehran University of Medical Sciences, 2019)
Background: We aimed to elucidate the preventive effects of taurine against osteopenia in ovariectomized (OVX) rats and the mechanisms by which taurine regulates osteoblastogenesis in vitro and in vivo. Methods: The effects of the taurine on human osteoblast MG-63 cell differentiation and osteoblastogenesis effect in OVX rat were examined Konkuk University in 2018 by evaluating osteoblast differentiation, and expression of osteoblast-specific factors by western blotting analysis. Results: Taurine supplementation significantly improved alkaline phosphatase (ALP) activity and mineralization in a concentration-dependent manner. Further, taurine induced the expression of osteogenic growth factors such as bone morphogenetic protein-2 (BMP-2), runt-related transcription factor 2 (RUNX2), small mothers against decapentaplegic 1/5/8 (SMAD1/5/8), wingless-type MMTV integration site family member 3A (Wnt3a), and collagen type 1 (COL-1) via mitogen-activated protein kinase (MAPK) and serine/threonine protein kinase (Akt). Moreover, the RUNX2 activity of the taurine-treated group was enhanced by protein-protein interactions such as Wnt3a-induced p-AKT/RUNX2 and BMP-mediated SMADs/MAPK/RUNX2 interactions. Conclusion: Our in vitro and in vivo results suggested that taurine can be considered as a potential therapeutic candidate agent for preventing bone loss in postmenopausal osteoporosis.